Uma nova versão sobre a oferta de moeda no Plano de Ação Econômica do Governo (PAEG) - Lucinda, Cláudio Ribeiro; Arvate, Paulo Roberto (Estudos Econômicos (São Paulo), 2005)
The control of the money supply was one of the most important instruments used in the carrying out of the monetary policy designed by the author of PAEG (1964/1966). Although the inflation has been controlled, the targets for monetary supply have not been reached. Pastore (1973, 1973a), Lara Resente (1982) and Cysne (1993) disaggee both on the reasons for that and the timing of the relevant facts. With a Time Series analysis it was possible to investigate what really happened with the money supply. The main conclusions are: a) During the PAEG, only one important structural change had happened (July 1965); other breaks have happened before the plan; b) although all of these authors agree with the role played by the money financing of Treasury, the credit supplied by Banco do Brasil as Monetary Authority is the best candidate in explaining the behavior of the Money Supply during the plan; c) the credit supplied by the Commercial Banks to the private sector had not any role in the determination of money supply during the period and d) the role of international reserves described by the authors is different from what really happened. The use of data on reserves other than those made available by SUMOC in real terms turned impossible a more precise work by these authors.